Postpartum depression during the COVID-19 pandemic: an umbrella review and meta-analyses - Sahebi, Ali; Kheiry, Maryam; Abdi, Kame; Qomi, Mahla; Golitaleb, Mohamad (Frontiers in Psychiatry, 2024)
Introduction The COVID-19 pandemic has significantly increased anxiety, stress, and depression, which could have harmful consequences for pregnant women. Therefore, this study aimed to investigate the prevalence of postpartum depression during COVID-19 using an umbrella review and meta-analysis. Methods The current study followed the PRISMA guideline and utilized data from various sources such as PubMed, Scopus, Web of Science, and Google Scholar. The searches were conducted without a time limit until the end of May 2023. Meta-analysis was performed using the random effects model, heterogeneity was assessed using the I2 index, and publication bias was evaluated using Begg’s test. Data analysis was carried out using STATA software (version 15). Results In this study, 243 articles were initially identified. Only meta-analysis studies that reported PPD during COVID-19 were included. After quality assessment, nine papers were selected for the meta-analysis stage. The study found that the prevalence postpartum depression (PPD) was 25.27% (95% CI = 23.66–27.86, I2 = 0.0%, p = 0.549). Conclusion The findings of this study revealed that the incidence of PPD during the COVID-19 pandemic was relatively high. To decrease mental health issues among pregnant and postpartum women, healthcare professionals should implement community programs aimed at preventing, promptly identifying, and providing appropriate intervention for pregnant women. This is crucial as pregnant women are particularly vulnerable to psychological distress during infectious disease outbreaks.